2008
DOI: 10.1890/06-1900.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Trends in Fish Mercury From a Mine‐dominated Ecosystem: Clear Lake, California

Abstract: Abstract. Clear Lake, California, USA, receives acid mine drainage and mercury (Hg) from the Sulphur Bank Mercury Mine, a U.S. Environmental Protection Agency (U.S. EPA) Superfund Site that was active intermittently from 1873 to 1957 and partially remediated in 1992. Mercury concentrations were analyzed primarily in four species of Clear Lake fishes: inland silversides (Menidia beryllina, planktivore), common carp (Cyprinus carpio, benthic scavenger/omnivore), channel catfish (Ictalurus punctatus, benthic omni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
(48 reference statements)
5
27
0
Order By: Relevance
“…The rapid elimination of IoHg relative to MeHg (three to five times faster) is also consistent with the rapid reduction of concentrations upon resumption of zooplankton foraging (Trudel andRasmussen 1997, Wang andWong 2003). Limited data for silversides from Clear Lake indicate that the percentage of TotHg as MeHg is highly variable (20-60%) and the proportion of MeHg is relatively low in comparison to larger fish from the lake (Suchanek et al 2008d ).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The rapid elimination of IoHg relative to MeHg (three to five times faster) is also consistent with the rapid reduction of concentrations upon resumption of zooplankton foraging (Trudel andRasmussen 1997, Wang andWong 2003). Limited data for silversides from Clear Lake indicate that the percentage of TotHg as MeHg is highly variable (20-60%) and the proportion of MeHg is relatively low in comparison to larger fish from the lake (Suchanek et al 2008d ).…”
Section: Discussionsupporting
confidence: 55%
“…1), an abandoned Hg mine that was responsible for ;100 Mg of Hg being deposited into the sediments between 1872 and 1957 (Suchanek et al 2003. Although the relative proportion of MeHg to total (primarily inorganic) Hg (TotHg) is low compared to other contaminated sites (Suchanek et al 2008a) in the lake are still commonly found with muscle tissue concentrations of 1.0-1.5 lg/g (ppm) wet mass (WM), and a human consumption advisory based on Hg has been in effect since 1986 (Suchanek et al 2008d, e).…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other chemical analyses of most feathers by X-ray fluorescence (XRF) has already been described by Cahill et al (1997), where total Hg is reported, although MeHg dominates feather residues (Thompson andFurness 1989a, b, Cahill et al 1997). Methylmercury also dominates total Hg (TotHg) residues in various Clear Lake fish species (Suchanek et al 2008c) selected as prey by these two important piscivorous birds. Mercury concentrations derived from both of these analytical methods are comparable (see Cahill et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Osprey and grebe feather residues (left y-axis; means 6 SE) over time plotted over residue levels in juvenile largemouth bass (right y-axis) from the Oaks Arm of Clear Lake (bass residue data are taken from Suchanek et al [2008c]). Sample sizes are given in Results and discussion: Osprey residues .…”
Section: Fig 2 Adultmentioning
confidence: 99%